2018
DOI: 10.31328/wy.v1i2.743
|View full text |Cite
|
Sign up to set email alerts
|

Budaya Malu Pada Masyarakat Tengger Dan Pengaruhnya Terhadap Budaya Hukum Penghindaran Konflik

Abstract: This shame culture is developed and maintained to serve as a means of traditional social control / social control so that the Tengger people always behave in accordance with Tengger norms and customs so as to avoid conflict. Culture of shame in Tengger society greatly influences its legal culture, that influence can be seen / manifested in never conflicts. The efforts of the Tengger people to maintain their shame culture through a social control system in the form of: (a) religious education; (b) Education in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…One of the most important aspects of legal culture is "shame culture," which is the most important part of Indonesian society's eastern customs (Negara, 2018). Shame Culture is a culture that reflects that a person has no shame when committing an offence, except when the offence is known to the public.…”
Section: Public Interest Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most important aspects of legal culture is "shame culture," which is the most important part of Indonesian society's eastern customs (Negara, 2018). Shame Culture is a culture that reflects that a person has no shame when committing an offence, except when the offence is known to the public.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…The culture of shame ingrained in society has become a social institution. In a culture of shame, a form of social institution is a feeling of loss of public trust, which is seen as a form of punishment that makes a person try to take stronger self-control actions that violate laws and other social norms (Negara, 2018). Reflecting on the culture of shame in contemporary Indonesia, reality reveals that this nation steeped in eastern values appears to have suffered degradation in upholding its culture of shame.…”
Section: Public Interest Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue is a feeling of shame for people who, for example, lack in one thing (mainly in the matter of property, perhaps also intelligence, or appearance). One feels that he is facing with someone who is more than himself [12].…”
Section: Shame Culturementioning
confidence: 99%
“…Other research focused on Ngadas [15] [16] highlighted harmony and tolerance as the identity of the Tenggerese in Ngadas. Another research [17] shows a culture of shame in Tengger characters, making them less likely to conflict internally and externally. Meanwhile, another study has also revealed changes in farming due to various changes [18].…”
Section: Introductionmentioning
confidence: 99%